2017
DOI: 10.1186/s12931-016-0493-6
|View full text |Cite
|
Sign up to set email alerts
|

Gene profile of fibroblasts identify relation of CCL8 with idiopathic pulmonary fibrosis

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is characterized by the complex interaction of cells involved in chronic inflammation and fibrosis. Global gene expression of a homogenous cell population will identify novel candidate genes.MethodsGene expression of fibroblasts derived from lung tissues (8 IPF and 4 controls) was profiled, and ontology and functional pathway were analyzed in the genes exhibiting >2 absolute fold changes with p-values < 0.05. CCL8 mRNA and protein levels were quantified using real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 49 publications
(58 reference statements)
2
44
0
Order By: Relevance
“…These differences include several signature molecules of IPF such as IGFBP-3 and lysyl oxidase [3]. Lee et al have reported that periostin expression is enhanced in fibroblasts derived from IPF patients, although expression levels of periostin vary among the clones [5]. We observed that some clones of IPF lung fibroblasts show high expression of periostin compared to normal lung fibroblasts, whereas there was no statistical significance because of the heterogeneity of IPF lung fibroblasts (Fig.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…These differences include several signature molecules of IPF such as IGFBP-3 and lysyl oxidase [3]. Lee et al have reported that periostin expression is enhanced in fibroblasts derived from IPF patients, although expression levels of periostin vary among the clones [5]. We observed that some clones of IPF lung fibroblasts show high expression of periostin compared to normal lung fibroblasts, whereas there was no statistical significance because of the heterogeneity of IPF lung fibroblasts (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…IPF fibroblasts display enhanced proliferation on polymerized collagen matrices [41]. Moreover, profiles of expressed genes differ between IPF patients and normal donors [3][4][5] . These differences include several signature molecules of IPF such as IGFBP-3 and lysyl oxidase [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibroblast cultures were obtained from 14 IPF patients and 10 NCs who underwent lung surgery, and the clinical information and laboratory data of these subjects were summarized in our previous study [10]. BAL fluid samples were obtained from patients with IPF (n � 84), NSIP (n � 9), hypersensitivity pneumonitis (n � 8), and sarcoidosis (n � 10), and the clinical characteristics of these patients are summarized in Table 1.…”
Section: Clinical Characteristics Of Study Groupsmentioning
confidence: 99%
“…Recently, global gene expression levels in lung tissues were compared to identify genes involved in the complex mechanism of IPF [6][7][8][9]. We also identified 178 of the total of 15,020 genes that were differentially expressed in lung fibroblasts from IPF patients and controls [10]. Among these genes, the mRNA expression of potassium voltage-gated channel subfamily J member 2 (KCNJ2) was 18.6-fold higher in IPF than control subjects.…”
Section: Introductionmentioning
confidence: 99%